Transformation of scientific knowledge into local knowledge: An analysis of the Mangupa-Upa tradition in the context of ESD-based education policy - Nurul Faizah Siregar (Journal of Character and Environment, 2026)
Background: The Mangupa-Upa tradition is part of the traditional ceremonies of the Batak Mandailing people, rich in cultural values, spirituality, and ecological symbolism. Amid global challenges such as environmental degradation and the crisis of cultural identity, an educational approach that integrates local knowledge is becoming increasingly relevant. This study aims to reconstruct elements of the Mangupa-Upa tradition into contextual biology learning resources that align with the direction of the Independent Curriculum and the principles of Education for Sustainable Development (ESD). Methods: The method used is a systematic literature review of various primary sources, including journal articles, scientific books, policy documents, and local cultural texts. The analysis was conducted thematically with a descriptive qualitative approach. Findings: The results of the study indicate that pangupa materials, such as betel, fish from seven rivers, old goats, and banana leaves, have symbolic meanings that can be reconstructed into scientific concepts in biology, such as biodiversity, the digestive system, the excretory system, plant and animal morphology, and the locomotion system. This integration of local knowledge supports the ethnopedagogical and ESD approaches, by instilling cultural values, environmental conservation, and strengthening local identity in the learning process. Furthermore, the reconstruction results indicate that a single local tradition can generate various biology learning topics relevant to the learning outcomes of phases E and F in the Independent Curriculum. Conclusion: The implications of this research suggest that transforming scientific knowledge into local forms such as Mangupa-Upa can be an effective pedagogical strategy to bridge the epistemological gap in formal education. This tradition serves not only as a cultural heritage but also as a transformative learning medium that strengthens students' scientific understanding in a contextual, participatory, and sustainable manner. Novelty/Originality of this article: The novelty of this study lies in reconstructing the Mangupa-Upa tradition into contextual biology learning resources aligned with the Independent Curriculum and ESD, demonstrating how a single local tradition generates multiple scientific learning themes.